Orthotopic bone regeneration within 3D printed bioceramic scaffolds with region-dependent porosity gradients in an equine model - Vindas Bolaños, Rafael (2020)
The clinical translation of three-dimensionally printed bioceramic scaffolds with tailored architectures holds great promise toward the regeneration of bone to heal critical-size defects. Herein, the long-term in vivo performance of printed hydrogel-ceramic composites made of methacrylatedoligocaprolactone-poloxamer and low-temperature self-setting calciumphosphates is assessed in a large animal model. Scaffolds printed with different internal architectures, displaying either a designed porosity gradient or a constant pore distribution, are implanted in equine tuber coxae critical size defects. Bone ingrowth is challenged and facilitated only from one direction via encasing the bioceramic in a polycaprolactone shell. After 7 months, total new bone volume and scaffold degradation are significantly greater in structures with constant porosity. Interestingly, gradient scaffolds show lower extent of remodeling and regeneration even in areas having the same porosity as the constant scaffolds. Low regeneration in distal regions from the interface with native bone impairs ossification in proximal regions of the construct, suggesting that anisotropic architectures modulate the cross-talk between distant cells within critical-size defects. The study provides key information on how engineered architectural patterns impact osteoregeneration in vivo, and also indicates the equine tuber coxae as promising orthotopic model for studying materials stimulating bone formation.